Influence of Photoperiod on The Relative Growth Rate of Hibiscus sabdariffa L - Muslihatin, Wirdhatul; Daesusi, Ruspeni (IPTEK The Journal for Technology and Science, 2025)
Red roselle (Hibiscus saddariffa L.) is a short day plant, this plant is only cultivated in a certain time period. There is a need to manipulate the environment where this plant can grow. The objective of this research was to study the influence of day length tothe relative growth rate (RGR) of H.sabdariffaL. Day length treatment was carried out by covering plants by black cover. Day length treatments were given in 8, 9,10, 11 and 12 hours of light exposure. Parameters measured were RGR of height plant, diameter of stem, number, and color of leaves. Harvesting was carried out when the flower crown fell or petals furl (the age of plants reached 3-4 months). The result of this research showed that highest plant was obtained at 10 hours day length (128.20 cm), the largest stem diameter growth rate was obtained at 8 hours (1.79 cm), number of leaves at 10 hours (183.40),and green color of leaves on 12 hours (scale 4). The highest RGR was obtained at 8 hours for all parameters except the height of plant and the color of leaves. Plant height, diameter and number of leaves at 8,9,10, and 11 hours of day length did not show significance difference. This showed that roselle is a short day length plant that grow optimal under 12 hours of day length.